Implementation of Academic Supervision through Islamic Religious Education Supervisors in Improving the Performance of Arabic Language Education Teachers at MTs Anwarul Hidayah - Pamuji, Slamet (Journal of Modern Islamic Studies and Civilization, 2024)
Academic supervision of PBA (Arabic Language Education) has an important role in PBA learning in accordance with the provisions of the specified standards. Thus, supervision is expected to improve the performance of PBA teachers in carrying out teaching and learning activities. The qualitative descriptive approach is prioritized by finding existing indicators. In finding existing information and indicators, data collection is more on data collection methods in the form of interviews, documentation, with analysis focused on listening, watching, interacting, asking, talking, exploring, taking important notes on matters relating to the academic supervision of PAI supervisors to improve PBA teacher performance. On the other hand, in reality, supervision is only related to administration rather than judging as a teacher. The assessment is only focused on administration, while the assessment of teacher competence in carrying out learning is not too seen and even prioritized. Assessment and supervision that is only concerned with administration does not make teachers enthusiastic in carrying out their duties as teachers. For this reason, a teacher needs guidance and supervision to assess the level of performance